Real‐time reverse osmosis monitoring for antiscalant dose selection in advanced treatment of wastewater. Issue 5 (5th October 2020) - Rahardianto, Anditya; Gu, Han; Khan, Bilal M.; Plumlee, Megan H.
Abstract: A new methodology was developed for rapid antiscalant dose optimization using the RO‐Spotlight™ real‐time membrane surface fouling imaging system. The approach relied on the sequential step‐down of antiscalant dose in a pilot reverse osmosis (RO) system to detect fouling onset and progression, requiring a tracking method of high sensitivity beyond that of indirect monitoring of permeate flux decline. The RO membrane monitoring system with its RO cell was interfaced with the pilot RO unit to treat microfiltered municipal wastewater. The pilot RO study, conducted at a 100‐mgd full‐scale advanced purification facility, demonstrated the feasibility for 26% antiscalant dose (hence chemical cost) reduction from the level deployed at the full‐scale plant. The optimal effective dose was determined at a significantly shorter period compared with prolonged piloting approaches on the basis of the monitoring of permeate flux decline. Continuous membrane monitoring can also provide immediate feedback regarding system performance degradation before the progression of significant fouling.